Hybrid firely and particle swarm optimisation algorithm for optimal dimming level and energy saving in lecturer’s room - Nik Ahmad, Nik Sahidah (2022)
The lighting system is one of the main systems in buildings and contributes to the usage of a considerable amount of energy. Therefore, the daylight harvesting system (DHS) is vital in lighting systems to control and minimise energy consumption from artificial lighting. The main factor for employee comfort in workplaces is the lighting system, where it can provide productivity and reduce stress when employees are working if they are getting enough lighting. There are many types of lighting systems and these systems have different performances in terms of energy efficiency, radiated heat, power consumption and lifetime. The optimisation of artificial lighting is required in order to achieve the optimal dimming level for minimising the energy consumption in buildings. To achieve the optimisation, a good, efficient and fast simulation algorithm is required. Thus, this research proposed a hybrid firefly and particle swarm optimisation (HFPSO) algorithm to solve the energy consumption and visual comfort problem by dimming-level minimisation. In order to identify the optimal dimming level, energy consumption, simulation time and luminaire performance, this research work presents the comparison between light-emitting diode (LED) and fluorescent luminaires using the HFPSO algorithm and using the particle swarm optimisation (PSO) algorithm and the firefly algorithm (FA). The comparison results showed that the superior performance of the HFPSO algorithm for the LED luminaire compared with that for existing luminaires, with significant energy savings of up to 64.2% and fully satisfying the average illuminance according to the Malaysian Standard MS-1525. The average simulation time for the LED luminaire was faster by up to 4.9% compared with the fluorescent luminaire. The average simulation time using the proposed HFPSO algorithm for the LED luminaire was faster by up to 7.6% than that for the fluorescent luminaire, compared with 4% and 3.6% faster using the PSO and FA methods, respectively. Therefore, the LED luminaire had the lowest dimming level and better performance in energy savings compared with those of the fluorescent luminaire by using the proposed method.